(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Football is one of the most popular sports among elementary school students and requires the mastery of various technical and physical components, including dribbling and balance. Balance plays a crucial role in maintaining body stability during movement, particularly when performing dribbling tasks that involve rapid changes of direction and ball control. However, empirical evidence regarding the influence of balance on dribbling performance among elementary school students remains limited, especially within the context of football extracurricular activities in Makassar. Therefore, this study aimed to analyze the influence of balance on the dribbling skills of students participating in football extracurricular activities at SD Inpres Mallengkeri I Makassar. This study employed a quantitative approach using a one-group pre-test–post-test design. The sample consisted of 15 fifth- and sixth-grade male students who actively participated in football extracurricular activities. Balance was measured using the Stork Balance Stand Test, while dribbling performance was assessed through a Zig-Zag Cone Dribbling Test involving six cones arranged 1.5 meters apart. Data were analyzed using Pearson Product-Moment correlation and simple regression analysis at a significance level of α = 0.05. The results revealed a very strong and significant relationship between balance and dribbling performance, with a correlation coefficient of r = 0.917, exceeding the critical value of r-table = 0.514. The significance value was p = 0.000 (< 0.05), indicating a statistically significant influence. The coefficient of determination (R²) was 0.841, demonstrating that balance contributed 84.1% to dribbling performance. Furthermore, the mean balance score improved from 18.40 seconds during the pre-test to 24.73 seconds during the post-test. In conclusion, balance significantly influences dribbling skills among elementary school football participants. Therefore, structured balance training should be systematically integrated into football extracurricular programs to enhance students’ technical performance and overall motor development.